Ethnic Influence Against Land Use Patterns and Its Contribution to Community Income in The Aketajawe Lolobata National Park (Pengaruh Etnis Terhadap Pola Pemanfaatan Lahan Dan Kontribusinya Bagi Pendapatan Masyarakat Di Taman Nasional Aketajawe Lolobata) - Lis Nurrani; Halidah Halidah; Supratman Tabba (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2015)
Buffer zone management is an integrated practice of managing forest and agriculture land based on biophysical nature of region and social-culture combination to obtain an optimum forest and agriculture products that support local livelihood economy. The study was to identify the community land use patterns that shapes the buffer zone of Aketajawe Lolobata National Park particularly at Aketajawe block. Sampling villages were determined by stratification based on the distance from the National Park boundary which varied between <3,3-5, and > 5 km. The purposive random sampling was chosen 82 respondents to be interviewed. Land use pattern which applied by communities were divided into six groups according to cultivated commodities i.e. community forest, mixed garden, monoculture garden, intercropping garden, horticulture and rice fields. The differences of these patterns were influenced by background and origin of communities. The indigenous people of Halmahera island used their land as mixed garden while the settler used theirs as rice field and horticulture. Based on the land cover quality, mixed garden pattern was more similar to forest vegetation than another pattern. Rice field pattern gave the largest economic contribution while community forest gave the lowest contribution to the farmer’s income.